2016
DOI: 10.1364/oe.24.028945
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of white for displays under dark- and chromatic-adapted conditions

Abstract: This study aims to investigate the white perception of mobile display devices under dark-adapted and chromatic-adapted conditions. The white perception was modeled with error ellipses and bivariate Gaussian distributions. The dark-adapted white encompassed a rather large area centered around 7300 K, slightly above the Planckian locus. The chromatic-adapted whites were highly dependent on the ambient illuminant, and were not parallel to the Planckian locus. Combined, the white region encompassing 6179 to 7479 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
6
14
0
Order By: Relevance
“…The largest axis was orientated along the blackbody / daylight (cerulean [Bosten 2012]) locus, in agreement with several other studies [Beer and others 2006;Bosten and others 2015;Choi and Suk 2016], suggesting that the visual system is tuned to the statistics of natural scenes [Bosten and others 2015;Chauhan and others 2014;McDermott and Webster 2012;Panorgias and others 2012;Pearce and others 2014;Witzel and others 2011]. These larger tolerances for the perception of white along the cerulean line could, for example, be explained by the large natural variation of daylight (and hence, in addition, absolute object colors) along this yellow-blue axis compared to the orthogonal direction.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The largest axis was orientated along the blackbody / daylight (cerulean [Bosten 2012]) locus, in agreement with several other studies [Beer and others 2006;Bosten and others 2015;Choi and Suk 2016], suggesting that the visual system is tuned to the statistics of natural scenes [Bosten and others 2015;Chauhan and others 2014;McDermott and Webster 2012;Panorgias and others 2012;Pearce and others 2014;Witzel and others 2011]. These larger tolerances for the perception of white along the cerulean line could, for example, be explained by the large natural variation of daylight (and hence, in addition, absolute object colors) along this yellow-blue axis compared to the orthogonal direction.…”
Section: Introductionsupporting
confidence: 92%
“…The substantial differences observed between the UW-neutral and the CA-neutral loci confirm the rather wide variation in lines of white [Li and others 2016;Ohno and Fein 2013;Ohno and Oh 2016;Perz and others 2016;Rea and Freyssinier 2014] and unique and preferred white chromaticities [Chauhan and others 2014;Choi and Suk 2016;Feng and others 2016;Honjyo and Nonaka 1970;Hurvich and Jameson 1951;Kuriki 2006;Priest 1921;Smet and others 2014;Sternheim and Drum 1993;Valberg 1971;Wang and Wei 2017] reported in the literature. (For an easy comparison, both neutral loci have been plotted in Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Specifically, the results under the adapting conditions with an L w of 115 cd/m 2 , as shown in Fig. 3(a), were very similar to those in the past studies using self-luminous displays [5,10,[12][13][14][15][16][17]21], while the results under the adapting conditions with an L w of 900 cd/m 2 , as shown in Fig. 3(d), were very similar to those in the past studies using reflective surface color samples (e.g., Munsell samples or NCS samples) [8][9][10].…”
Section: Effect Of Adapting Luminance On Viewing Modesupporting
confidence: 85%
“…It was found that the chromaticities for producing the whitest appearance were significantly different for these two viewing media. When using self-luminous displays, the chromaticities for producing white appearance were found to be shifted along the Planckian locus towards a higher CCT [5,10,[12][13][14][15][16][17]; when using reflective surface colors samples, the chromaticities for producing white appearance were found much closer to the chromaticities of the adapting conditions [7][8][9][10]. Such a difference has been commonly attributed to the different degrees of chromatic adaptation caused by the two viewing media.…”
Section: Introductionmentioning
confidence: 99%
“…Zhai and Luo carried out an experiment using both surface color stimuli and self‐luminous color stimuli to collect corresponding white colors under the adapting conditions with various CCT and D uv levels and found a lower degree of chromatic adaptation when viewing self‐luminous color stimuli 9 . A similar trend for self‐luminous color stimuli was also found in Choi and Suk 10 and Huang et al 11 …”
Section: Introductionsupporting
confidence: 56%